Kinematics and Singularity Analysis of a Planar 3-PRP Type Parallel Manipulator - An Ziming; Zhu Dachang (Jixie chuandong)
A planar 3-PRP type parallel manipulator with three symmetrical limbs structure in the plane is proposed,and each limb consists of a prismatic joint is connected to a basement,one prismatic joint is connected with the moving platform,and two prismatic joints connected through a revolute joint.By using vector analysis method,the inverse and forward kinematics solution of planar 3-PRP type parallel manipulator are solved,and the Jacobian matrix is analyzed with the velocity and singular isotropic configuration.The results show that the planar 3-PRP type parallel manipulator without singularity in the work area,and through the modify motion parameters can improve the motion accuracy.